Myeloid cell leukemia-1: a formidable barrier to anticancer therapeutics and the quest of targeting it - Prasad Sulkshane; Tanuja Teni (Exploration of Targeted Anti-tumor Therapy, 2022)
The antiapoptotic B cell lymphoma-2 (Bcl-2) family members are apical regulators of the intrinsic pathway of apoptosis that orchestrate mitochondrial outer membrane permeabilization (MOMP) through interactions with their proapoptotic counterparts. Overexpression of antiapoptotic Bcl-2 family proteins has been linked to therapy resistance and poor prognosis in diverse cancers. Among the antiapoptotic Bcl-2 family members, predominant overexpression of the prosurvival myeloid cell leukemia-1 (Mcl-1) has been reported in a myriad of hematological malignancies and solid tumors, contributing to therapy resistance and poor outcomes, thus making it a potential druggable target. The unique structure of Mcl-1 and its complex regulatory mechanism makes it an adaptive prosurvival switch that ensures tumor cell survival despite therapeutic intervention. This review focusses on diverse mechanisms adopted by tumor cells to maintain sustained elevated levels of Mcl-1 and how high Mcl-1 levels contribute to resistance in conventional as well as targeted therapies. Moreover, recent developments in the Mcl-1-targeted therapeutics and the underlying challenges and considerations in designing novel Mcl-1 inhibitors are also discussed.